Bioactive Compound Contents and Antioxidant Activity of Purified Red Sorghum Pericarp Extract by Membrane Ultrafiltration Process - Afandy, Moh. A.; Sediawan, Wahyudi B.; Hidayat, Muslikhin; Susanti, Devi Y.; Sawali, Fikrah D. I. (Jurnal Akademika Kimia, 2023)
Sorghum plants contain bioactive compounds such as phenolic compounds and proanthocyanidins. The presence of these compounds is extremely valuable for use as antioxidants in health care. This study aims to determine the total phenolic content, total proanthocyanidin content, and antioxidant activity of purified red sorghum extract using the ultrafiltration membrane method with different transmembrane pressure. At pressures of 8, 9, and 10 Bar, an ultrafiltration process was carried out using a polyethersulfone (PES) membrane with a molecular weight cut-off size of 10 kDa. The total phenolic content was determined using the Folin-Ciocalteu method and identified using UV-Vis spectrophotometry at 760 nm. Total proanthocyanidin content was measured using the acid-butanol method and then analyzed using UV-Vis spectrophotometry at 550 nm. The DPPH (2,2-diphenyl-2-picrylhydrazyl) method will be used to determine the antioxidant activity of purified red sorghum extract. The results of the measurements show that the higher the transmembrane pressure, the higher the concentration of phenolic and proanthocyanidins content, and that the purified red sorghum extract has a high antioxidant value (IC50 = 66.852 ppm).